RagA, an mTORC1 activator, interacts with a hedgehog signaling protein, WDR35/IFT121. (15th January 2019) - Sekiguchi, Takeshi; Furuno, Nobuaki; Ishii, Takashi; Hirose, Eiji; Sekiguchi, Fumiko; Wang, Yonggang; Kobayashi, Hideki
Abstract: Small Ras‐like GTPases act as molecular switches for various signal transduction pathways. RagA, RagB/RagC and RagD are small Ras‐like GTPases that play regulatory roles in mTORC1. Lack of proper activation of mTORC1 can lead to diseases, such as cancer and diabetes. In this study, we found an interaction between RagA and WDR35. Mutations of WDR35 may cause genetic diseases including Sensenbrenner syndrome. WDR35 seems to be a hedgehog signaling protein with a possible ciliary function and a possible upstream regulator of RagA. RagB is a homologue of RagA and is also associated with WDR35. WDR35 is present in the endoplasmic reticulum, but usually not in lysosomes, where Rag family proteins act as an mTORC1 switch. Over‐expression of WDR35 results in decreased phosphorylation of ribosome S6 protein in a RagA‐, RagB‐ and RagC‐dependent manner. Thus, WDR35 is associated with RagA, RagB and RagC and might negatively influence mTORC1 activity. Abstract : WDR35, which causes genetic diseases including Sensenbrenner syndrome and seems to be a hedgehog signaling protein and a protein with a possible ciliary function, might be possible upstream regulator of RagA. WDR35 associates with RagA, RagB and RagC and might negatively influence mTORC1 activity.